Knowledge about anesthesia and the role of anesthesiologists among Jeddah citizens - Bagabas, Ahmed M.; Ashi, Mooataz Mohammed; Alamoudi, Ahmed O.; Alaidarous, Sameer A.; Filemban, Sohaib K.; Bahaziq, Wadeeah K. (International Journal of Research in Medical Sciences, 2017)
Background: The anesthesiologist has a vital role in the operating theatres. Awareness of the role of the anesthesiologist and the types of anesthesia is essential for every person. This study was made to estimate how much information the general population have about the anesthesiologist and the different types of anesthesia. Methods: This research was a cross sectional non-interventional study. The research team conducted a questionnaire in which each participant in the study was interviewed by the research team. The sample size was 159 participants. Results: From the participants,99 (62.2%) recognized the anesthesiologist as a specialized doctor who administers the anesthetics,62 (38.9%) know that the anesthesiologist has a role in resuscitating the patient with the team if crises occurred. However, 85 (53.4%) believe that the surgeon has the responsibility of postoperative pain management. Physicians were the source of knowledge for most participant’s information. Conclusions: A reasonable percentage of people appreciated the role of the anesthesiologist in administrating the anesthesia, however there is a lack of information about the role of the anesthesiologist intra and postoperatively. The need for more education for people about anesthesia is essential as the amount of information about anesthesia in general is rather low.